Surgery in Hypertensive Intracerebral Haematoma (ICH) Study of 49 Cases (TAJ: Journal of Teachers Association, 2009)
Surgery in hypertensive intra cerebral haematoma are still controversial. We treated 49 cases of intracerebral haematoma surgically from January 1995 to December 2005. Hypertensive haematomas are- putaminal, thalamic, cerebellar, pontine haemorrhage and subcortical. These haematomas are mild, moderate and severe type. We operated ICH, where the diameters of haematomas were more than 3cm. Outcome was assessed on basis of activity of daily living (ADL). Male to female ratio was 5:2, Patients age ranged 45 to 72 years. All patients presented with unconscious or semiconscious stage, 100% patients had CT scan of brain. In this study of 49 cases 20(40.82%) had ADL II, 24 (45.82%) had ADL III, 1 (2.4%) had ADL IV. Death occurred in 04 (8.16%) cases. doi: 10.3329/taj.v20i2.3073 TAJ 2007; 20(2): 127-128